2018
DOI: 10.3988/jcn.2018.14.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Chronic Oxaliplatin-Induced Neuropathy in Patients with Colon Cancer: Long-Term Outcomes and Predictors of Severe Oxaliplatin-Induced Neuropathy

Abstract: Background and PurposeThe objective of this study was to determine the incidence and long-term outcomes of oxaliplatin-induced peripheral neuropathy (OIPN), as well as predictors of its severe form.MethodsSixty-nine patients who were taking oxaliplatin for colon cancer were prospectively followed prior to starting chemotherapy and after 4, 8, and 12 cycles of chemotherapy. Thirty-six patients completed the follow-up at 1 year after the end of chemotherapy. The patients were assessed using clinical assessment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [ 17 , 41 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 85%
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [ 17 , 41 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 85%
“…A prospective study of Korean colorectal cancer patients treated with 12 cycles of adjuvant FOLFOX revealed that 94% showed signs of OIPN after the completion of treatment, and 14% of patients showed grade 3 OIPN. 11) OIPN persisted in 64% of patients 1 year after the end of treatment, with 11% of patients showing grade 3 toxicity, and the frequency and severity of OIPN increased with repeated cycles of chemotherapy. 11) Because there is no specific method to prevent OIPN and treatment entails only conservative management, there is continued concern about how to reduce the use of oxaliplatin.…”
Section: Discussionmentioning
confidence: 97%
“…11) OIPN persisted in 64% of patients 1 year after the end of treatment, with 11% of patients showing grade 3 toxicity, and the frequency and severity of OIPN increased with repeated cycles of chemotherapy. 11) Because there is no specific method to prevent OIPN and treatment entails only conservative management, there is continued concern about how to reduce the use of oxaliplatin. 12) One way to reduce the frequency and severity of OIPN may be to reduce the number of chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, TRPA1 blockers or genetic ablation decreased nociceptive changes observed in animal models of neuropathic pain [60,154,155,156]. Another standard model of neuropathic pain is the one induced by the administration of chemotherapy drugs that may produce, as side effects, intense cold and mechanical hyperalgesia and/or allodynia, limiting administration to patients [157,158]. Similar to nerve injury models, the blockage of TRPA1 counteracted pain in several models of chemotherapy-induced neuropathic pain [159,160].…”
Section: Trpa1 In Neuropathic Painmentioning
confidence: 99%